FERMENTABILITY OF Limosilactobacillus fermentum YU2301 FOR PLANT-BASED MILKS - Vy, Dinh Thi Thanh; Loan, Le Thi; Hieu, Vo Hoai (HUIT Journal of Science, 2024)
Limosilactobacillus fermentum YU2301 has the ability to ferment plant-based kinds of milk such as soy milk, peanut milk, red bean milk, lotus seed milk, and coconut milk. During the fermentation process, the pH of the kinds of milk gradually decreased and the lactic acid content gradually increased, at 24 hour the pH of the kinds of milk was below 4.5 and the lactic acid content was above 0.3 g/100mL. In addition, when using L. fermentum YU2301 to ferment plant milk, the ability to reduce DPPH free radicals increased, at 24 hours, the percentage of free radical scavenging was highest with 91.67%±2.08 (bean milk) peanuts with 1% v/v strains participating in fermentation) and 94.44%±1.20 (coconut milk with 2% v/v strains participating in fermentation). Total phenolic content decreased significantly with fermentation time. The density of L. fermentum YU2301 increased with fermentation time in all kinds of milk, up to 24 hours the concentration of L. fermentum YU2301 reached over 108 CFU/mL.